Sustainable Coffee Marketing:Challenges and the Way Forward - M. K., Gana Shruthy; Kumar, Parmod; Yadav, Jyothi Pravin (Indian Journal of Marketing, 2016)
This paper analyzed markets for sustainable coffee by taking into account five individual sustainable coffee initiatives, that is, 4C (Common Codes for Coffee Community), Utz, Rainforest Alliance (RFA), Fair-trade Labeling Organization (FLO), and Organic coffee. The sustainable coffee production experienced a phenomenal growth over the past decade. However, the volumes of sales represent only a minor portion of production. Less than 25% of sustainable coffee produced was 'actually sold' as sustainable, while the remaining was just sold as 'ordinary' conventional coffee, without receiving any extra market benefits. Among the individual coffee certification initiatives, 4C (Common Codes for Coffee Community) signaled a more serious over-supply in the global market, wherein only 6% of its overall sustainable production was actually sold as sustainable over 2008-12. During the same period, Utz coffee certification could sell 25%, Rainforest Alliance (RFA) could trade 50%, and organic certified coffee could sell 55% of its standard-compliant production as sustainable. The study revealed that global sustainable coffee market is characterized by massive 'over-supply'; demand being a major constraint. Underpinning this issue is the need for sustainable coffee market. The current market challenge is to stabilize mismatch between demand and supply for sustainable coffee. From a sustainable development perspective, this remains a serious matter of concern for policy makers, public institutions, and multi-stakeholders to engage in market-based control mechanism in constructing effective 'supply- management base' as a strategy for price-stabilization and to enhance further sustainable growth. At a micro level in India, coffee certification is still at an infancy stage, contributing to just 2% of total global sustainable production. The Indian Coffee Board and apex coffee organizations need to work in this direction to encourage both sustainable production and marketing, so as to assist growers in assessing preferential market benefits, besides supporting high quality 'Indian coffee' being traded at both the global and domestic levels.